RUPA TOPENG KLATEN KOLEKSI BAMBANG SUWARNO - Bening Tri Suwasono (Pascasarjana Institut Seni Indonesia Surakarta, 2013)
This article results from research that focuses on study how the Klaten masks. How the symbolic meanings of the Klatenmaska. How the appearce of the Klaten masks Bambang Suwarno’s collection. The aim of the research was to discover andexplain the existence of the Klaten masks, symbolic meanings, and appearce of the Klaten masks Bambang Suwarno’scollection. The method used for the study was a qualitative research method, the interaction analysis approach which wasstructured to cover a historical study, symbolic meanings, and analysis Klaten masks Bambang Suwarno’s collection (Panji,Candrakirana, Klana, Penthul, Tembem), and conclusion. The results was studied of the details as part of the masks likes eyeshape, eyebrows, nose, mouth, ornaments and other. The symbolic meanings of the Klaten masks is the connection betweenthe microcosm and macrocosm embodied in the characters and colors.Keywords: Klaten mask, symbolic meaning, characters.